Polymer surface copper coating method

By coarsely treating the polymer surface and using a copper plating solution containing citric acid for copper plating, the problems of low copper cladding rate and low binding force in the prior art are solved, and efficient and lightweight copper cladding effect is achieved , improve product quality.

CN119392230APending Publication Date: 2025-02-07SHANGHAI ENERGY NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411524706.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the copper cladding rate on the surface of the polymer is low, the bonding force between the copper cladding layer and the polymer is not high, making it difficult to achieve light weight, resulting in insufficient product quality.

Method used

The polymer surface is coated with copper using a method including a roughening step and a copper plating step. The roughening step prepares the surface by plasma treatment and corona treatment, and the copper plating step uses a copper plating solution containing complexing components, including citric acid and its salts, to increase the deposition rate and binding force of the copper.

Benefits of technology

The deposition rate of copper is improved, the bonding force between the copper clad layer and the polymer is enhanced, and the weight is achieved, reducing time and cost is reduced, while improving the quality and oxidation resistance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392230A_ABST
    Figure CN119392230A_ABST
Patent Text Reader

Abstract

The invention provides a method for coating copper on the surface of a polymer, which is characterized in that a coarsening step and a copper plating step are carried out on the polymer, a copper plating solution is used in the copper plating step, and the copper plating solution comprises plant acid; therefore, the problems of low copper coating rate, low binding force between the copper layer and the polymer and the like in the traditional technology can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present technology relates to the field of polymers, and in particular to a method for copper plating on a polymer surface. Background Art

[0002] Due to the rapid development of the electronic information and energy industries, there is a demand for composite materials in integrated circuits, lithium-ion battery collectors, advanced packaging, energy storage devices, electromagnetic shielding equipment, construction industry, tools and molds, IT industry circuit boards, vehicle surface modification, wireless communication, aerospace, medical chemicals, electrochemical sensors, low-altitude aircraft and other fields.

[0003] For example, porous polymer-based copper composite materials are copper-clad materials on plastic, glass, ceramic or textile. In terms of functionality, they have the excellent properties of copper while achieving lightweight and cost-reducing purposes, making them a research hotspot for copper composite materials in recent years. For example, they can be used in conductive interconnection, electromagnetic shielding, thermal conductivity and heat dissipation, decorative protection and other aspects of electronic products, and they play a very important role.

[0004] However, with the current existing technology, there are still problems such as low copper plating rate, low bonding strength between the copper plating layer and the polymer, and difficulty in lightweighting, which results in longer copper plating time and insufficient product quality. Summary of the invention

[0005] In order to solve the above problems, the present invention discloses a fast and efficient method. To coat the surface of the polymer with copper.

[0006] The present invention provides a method for copper coating on a polymer surface, comprising the following steps: A, a roughening step: performing a first roughening treatment on the polymer to obtain a roughened polymer; and B, a copper plating step: copper plating the roughened polymer using a copper plating solution to obtain a copper-coated polymer, wherein: The copper plating solution includes a complexing component, the complexing component includes a first plant acid, and the first plant acid includes citric acid, malic acid, glycolic acid, or tartaric acid.

[0007] In some embodiments, the complexing component further comprises a first phytate, wherein the first phytate comprises citrate, malate, glycolate, or tartrate.

[0008] In some embodiments, the first plant acid is citric acid and the first plant acid salt is potassium sodium tartrate.

[0009] In some embodiments, the mass ratio of the first phytic acid to the first phytate salt is 1:(0.5-2.0).

[0010] In some embodiments, the complexing component further comprises a complexing agent, and the complexing agent comprises disodium ethylenediaminetetraacetate, 2'2-bipyridine, and potassium ferrocyanide.

[0011] In some embodiments, the mass ratio of the first phytic acid to the first phytate salt to the chelating agent is 1:(0.5-2.0):(0.5-2.0).

[0012] In some embodiments, the mass ratio of the first plant acid to the disodium edetate is 1:(1.0-1.8).

[0013] In some embodiments, the copper plating solution further includes: a copper ion source, a pH adjuster, and a reducing agent.

[0014] In some embodiments, the first roughening treatment comprises plasma treatment, corona treatment, or a combination thereof.

[0015] In some embodiments, the first roughening treatment includes the plasma treatment and the corona treatment, wherein a ratio of a treatment time of the plasma treatment to a treatment time of the corona treatment is 3:(1-30).

[0016] In some embodiments, in the roughening step, a second roughening treatment is further performed after the first roughening treatment to obtain the roughened polymer.

[0017] In some embodiments, a sensitization step and an activation step are sequentially performed on the roughening polymer between the roughening step and the copper plating step.

[0018] In some embodiments, the polymer is subjected to a decontamination step before the roughening step. And between the sensitization step and the activation step, the roughened polymer is subjected to a water washing step.

[0019] In some embodiments, a decontamination solution is used in the decontamination step, which includes sodium hydroxide, sodium carbonate and a detergent, a sodium hydroxide aqueous solution with a mass fraction of 20-30% is used in the second roughening treatment, a stannous chloride aqueous solution with a concentration of 20-40 g / L is used in the sensitization step, deionized water with a temperature of 40-50°C is used in the washing step, and a palladium chloride aqueous solution with a concentration of 0.75-2 g / L is used in the activation step.

[0020] In some embodiments, the polymer includes: polyethylene, polytetrafluoroethylene, polyvinylidene fluoride, polyimide, polyethylene terephthalate, polypropylene, polysulfone, polydimethylsiloxane, polyamide, polystyrene, polyvinyl chloride, aramid, polyphenylene dicarboxylate, acrylonitrile butadiene styrene copolymer, polybutylene terephthalate, polyparaphenylene terephthalamide, polypropylene, polyamide urea, polyoxymethylene, epoxy resin, phenolic resin, silicone rubber, polycarbonate, polyvinyl alcohol, polyethylene glycol or any combination thereof.

[0021] The present invention further provides a copper-clad polymer, which is prepared by the above-mentioned method for copper-clad polymer surface.

[0022] The present invention further provides a copper plating solution, which comprises: a first plant acid and a first plant acid salt, wherein the first plant acid is citric acid, the first plant acid salt is potassium sodium tartrate, and the mass ratio of the first plant acid to the first plant acid salt is 1:(0.5-2.0).

[0023] In some embodiments, the copper plating solution further comprises disodium ethylenediaminetetraacetate, 2'2-bipyridine, and potassium ferrocyanide, wherein the mass ratio of the first plant acid to the disodium ethylenediaminetetraacetic acid is 1:(1.0-1.8).

[0024] In some embodiments, a copper-clad polymer can be obtained by sequentially subjecting the polymer to the above steps, including a decontamination step, a roughening step, a sensitization step, a water washing step, an activation step, and a copper plating step. Based on the effect of the roughening step and the copper plating solution, the beneficial effects of the present invention are produced, including but not limited to: (1) in the copper plating step, the copper deposition rate is improved, so that the time cost and equipment cost can be reduced; (2) the copper plating layer and the polymer are tightly bonded, and the product weight becomes lighter due to the reduced density of the copper-clad layer; (3) the polymer can be repeatedly copper-plated.

[0025] On the other hand, the present invention also provides a copper-clad polymer produced by the above-mentioned copper-clad method, and the above-mentioned copper plating solution, wherein the beneficial effects of the present invention include but are not limited to: the surface of the copper-clad polymer is flat, dense, and bright, and has excellent antioxidant properties and modification functions, and at the same time, its tensile strength is improved and its bending resistance is also improved; the properties of the copper plating solution are more stable.

[0026] Based on this, the problems of low copper coating rate, weak bonding strength between the copper coating layer and the polymer, and insufficient lightweight in traditional technologies can be solved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic diagram of the first step, regarding the method of copper coating on the polymer surface.

[0028] Figure 2 This is a schematic diagram of step 2, which is about the method of copper coating on the polymer surface.

[0029] Figure 3 This is a schematic diagram of step 3, which is about the method of copper coating on the polymer surface.

[0030] Figure 4 Schematic diagram of the copper-clad polymer structure.

[0031] Figure 5 SEM image of polymer base film after corona treatment.

[0032] Figure 6 This is the SEM image of the polymer base film after plasma treatment.

[0033] Figure 7 This is the SEM morphology of the copper cladding layer of Example 2.

[0034] Figure 8 This is an optical image of the copper clad layer of Example 3.

[0035] Fig. 9 This is the SEM morphology of the copper cladding layer of Example 3.

[0036] Fig.10 This is the optical morphology of the copper foil after copper plating in Comparative Example 2. DETAILED DESCRIPTION

[0037] The essential features of the present invention are further illustrated by combining the following embodiments.

[0038] In some embodiments, the present invention provides a method 1 for copper coating on a polymer surface, which is to copper-coat the surface of the polymer, that is, to perform a copper coating step S6, to produce a copper-coated polymer 2. Here, the polymer may include polyethylene, polytetrafluoroethylene, polyvinylidene fluoride, polyimide, polyethylene terephthalate, polypropylene, polysulfone, polydimethylsiloxane, polyamide, polystyrene, polyvinyl chloride, aramid, polyphenylene dicarboxylate, acrylonitrile butadiene styrene copolymer, polybutylene terephthalate, poly(p-phenylene terephthalamide), polypropylene, polyamide urea, polyoxymethylene, epoxy resin, phenolic resin, silicone rubber, polycarbonate, polyvinyl alcohol, polyethylene glycol, or any combination thereof.

[0039] From a macroscopic perspective, the polymer may be a non-metallic material, without limitation, and may be plastic, glass, ceramic or textile.

[0040] Please refer to Figure 1 In some embodiments, the method 1 for copper coating on a polymer surface further includes a pretreatment before the copper plating step S6; the pretreatment includes: a roughening step S2.

[0041] Please refer to Figure 2 In some embodiments, the polymer surface copper coating method 1 further includes a pretreatment before the copper plating step S6; the pretreatment further includes: a decontamination step S1, a sensitization step S3, a water washing step S4 and / or an activation step S5.

[0042] In some embodiments, preferably, the pretreatment sequentially comprises a decontamination step S1, a roughening step S2, a sensitization step S3, a water washing step S4 and an activation step S5.

[0043] The decontamination step S1 is preferably to perform ultrasonic decontamination on the polymer immersed in a decontamination liquid, and then use an alcohol aqueous solution to clean the polymer. Obviously, the specific frequency of the ultrasonic wave is not limited.

[0044] The decontamination liquid includes sodium hydroxide, sodium carbonate, or a detergent; preferably, the decontamination liquid includes 20-50 g / L of sodium hydroxide, 10-40 g / L of sodium carbonate, or 50-60 g / L of a detergent; wherein the decontamination step S1 uses a decontamination liquid at a temperature of 40-55°C and a soaking time of 15-20 minutes.

[0045] The alcohol aqueous solution includes 50-90% ethanol aqueous solution, preferably 75% ethanol aqueous solution.

[0046] Please refer to Figure 3 The roughening step S2 includes a first roughening treatment S21 and / or a second roughening treatment S22. Preferably, the roughening step S2 includes the first roughening treatment S21 and the second roughening treatment S22, and the first roughening treatment S21 precedes the second roughening treatment S22.

[0047] Please refer to Figure 3 The first roughening treatment S21 includes plasma treatment S211 and / or corona treatment S212. It can be known that the plasma treatment S211 or the corona treatment S212 can be performed selectively, the plasma treatment S211 is performed before the corona treatment S212, or the corona treatment S212 is performed before the plasma treatment S211.

[0048] The plasma treatment S211 can be repeated, and the corona treatment S212 can be repeated.

[0049] The plasma treatment S211 is to place the polymer in an ion chamber, The ion chamber is evacuated to 4.0-6.0×10 -2(Pa) Pa, and then introduce working gas so that the polymer is surrounded by the working gas.

[0050] The working power of the plasma treatment S211 is between 35-300 (watts) W, preferably between 50-250 W; the working gas includes: helium, argon, nitrogen, oxygen or a combination of the above gases, preferably nitrogen; the working temperature is 20-30°C; the processing time of the plasma treatment S211 is 0.5-10 minutes, preferably 0.5-3 minutes; the air pressure of the working gas atmosphere (working air pressure) is between 0.1-1.5 Pa.

[0051] The treatment voltage of the corona treatment S212 is 1-100 kv, preferably 2-70 kv; the treatment time of the corona treatment S212 is 0.5-8 minutes, preferably 1-5 minutes.

[0052] In some embodiments, the ratio of the treatment time of the plasma treatment S211 to the treatment time of the corona treatment S212 is 3:(1-30), preferably 3:(1-20).

[0053] In the second roughening treatment S22, a second roughening solution is used, which includes a sodium hydroxide (NaOH) solution; preferably, the mass fraction of the sodium hydroxide is 20-30%.

[0054] The second roughening treatment time is 3-15 minutes, preferably 5-10 minutes; the second roughening treatment temperature is 20-30°C, preferably 25°C.

[0055] In some embodiments, the polymer undergoes the roughening step S2 to become a roughened polymer, and then undergoes the sensitization step S3, the water washing step S4 and the activation step S5.

[0056] In the sensitization step S3, a sensitizing solution is used, which includes stannous chloride (SnCl 2 ); Preferably, the sensitizing solution comprises 20-40 g / L of stannous chloride and 20-30 mg / L of hydrogen chloride (HCl).

[0057] In the sensitization step S3, the sensitization time is 1-5 minutes, preferably 2-3 minutes; the sensitization temperature is 20-30°C, preferably 25°C.

[0058] In the water washing step S4, deionized water is used; preferably, the temperature of the deionized water is 40-50°C, preferably 45°C.

[0059] In the activation step S5, an activation solution is used, which includes palladium chloride (PdCl2 ); Preferably, the activation solution comprises 0.75-2 g / L of palladium chloride.

[0060] In the activation step S5, the activation time is 1-5 minutes, preferably 2-3 minutes; the activation temperature is 20-30°C, preferably 25°C.

[0061] It is worth noting that, in the sensitization step S3, the water washing step S4, and the activation step S5, when the polymer enters the water washing step S4 from the sensitization step S3, the tin (Sn) ions attached to the surface of the polymer will be hydrolyzed into Sn(OH)Cl, attached to the polymer in the form of a gel film, and facilitate the subsequent adsorption of palladium (Pd) ions including the activation step S5.

[0062] In some embodiments, the copper plating step S6 is to use a copper plating solution comprising a copper ion source, a complexing component, a reducing agent and a pH adjuster to copper plate the polymer.

[0063] The copper ion source includes copper sulfate, copper chloride, copper nitrate, copper acetate, or any combination thereof.

[0064] In some embodiments, the complexing component includes a complexing agent and / or a plant acid.

[0065] The complexing agent includes ammonia, ethylenediamine, disodium ethylenediaminetetraacetate, polyvinylpyrrolene, 2'2-bipyridine, potassium ferrocyanide or any combination thereof.

[0066] The plant acids include citric acid, malic acid, glycolic acid, and / or tartaric acid; it is understandable that the plant acids may exist in the form of their salts, or have water of crystallization to form plant acids or hydrated plant acids; it is also understandable that when the hydrated plant acids are dissolved in an aqueous solution, their ionic form is the same as that of the plant acids dissolved in an aqueous solution.

[0067] In some embodiments, the phytic acid comprises a first phytic acid and / or a first phytate salt.

[0068] In some embodiments, the first plant acid comprises: citric acid, malic acid, glycolic acid, or tartaric acid.

[0069] In some embodiments, the first phytate comprises citrate, malate, glycolate, or tartrate.

[0070] In some embodiments, the mass ratio of the first plant acid to the complexing agent is 1.0:(0.5-2.0).

[0071] In some embodiments, the mass ratio of the first phytic acid to the first phytate salt is 1.0:(0.5-2.0).

[0072] In some embodiments, the mass ratio of the first phytic acid to the first phytic acid salt to the chelating agent is 1:(0.5-2.0):(0.5-2.0).

[0073] In some embodiments, the mass of the first phytic acid is greater than the mass of the first phytate salt, and the mass of the first phytic acid is less than the mass of the complexing agent.

[0074] The reducing agent includes sodium hypophosphite, sodium borohydride, hydrazine, formic acid, or formaldehyde.

[0075] The pH adjuster includes sodium hydroxide, sulfuric acid, acetic acid, ammonia, hydrofluoric acid, or sodium carbonate.

[0076] In some embodiments, the copper ion source is copper sulfate; the complexing component includes a first plant acid, a first plant salt and a complexing agent, wherein the first plant acid is citric acid, the first plant salt is potassium sodium tartrate tetrahydrate, and the complexing agent is disodium ethylenediaminetetraacetic acid, 2'2-bipyridine, and potassium ferrocyanide; the reducing agent is formaldehyde; the pH value adjusting agent is sodium hydroxide.

[0077] In some embodiments, the copper plating solution has: the mass ratio of the first plant acid to the disodium ethylenediaminetetraacetic acid is 1.0:(1.0-1.8); the mass ratio of the 2'2-bipyridine to the potassium ferrocyanide is 1.0:(0.5-2.0); and the ratio of the total mass of the citric acid and the disodium ethylenediaminetetraacetic acid to the total mass of the 2'2-bipyridine and the potassium ferrocyanide is 1500:(0.5-1.5).

[0078] In some embodiments, the copper plating solution has: 8-12 g / L copper sulfate, 5-8 g / L sodium hydroxide, 20-30 g / L potassium sodium tartrate tetrahydrate, 30-40 g / L citric acid, 35-45 g / L disodium ethylenediaminetetraacetate, 10-20 mL / L formaldehyde, 10-40 mg / L 2'2-bipyridine, and 10-35 mg / L potassium ferrocyanide.

[0079] In some embodiments, the copper plating solution has: 8-12 g / L copper sulfate, 5-8 g / L sodium hydroxide, 30-40 g / L citric acid, 35-45 g / L disodium ethylenediaminetetraacetate, 10-20 mL / L of formaldehyde, 10-40 mg / L of 2'2-bipyridine, and 10-35 mg / L of potassium ferrocyanide.

[0080] In some embodiments, the copper plating solution has: 8-12 g / L copper sulfate, 5-8 g / L sodium hydroxide, 20-30 g / L potassium sodium tartrate tetrahydrate, 35-45 g / L disodium ethylenediaminetetraacetate, 10-20 mL / L formaldehyde, 10-40 mg / L 2'2-bipyridine, and 10-35 mg / L potassium ferrocyanide.

[0081] In the copper plating step S6, the copper plating time is 30-180 seconds, and the copper plating temperature is controlled at 25-55°C.

[0082] In some embodiments, the copper plating step S6 can be performed repeatedly.

[0083] In some embodiments, the copper plating solution can be reused. It is understood that when the copper plating solution contains citric acid and / or potassium sodium tartrate tetrahydrate, the copper plating solution has better stability, can be reused, and can be used in the copper plating step S6 when it is repeated.

[0084] The present invention provides a copper-clad polymer 2, which includes: a polymer; and a copper-clad layer 11, wherein the copper-clad layer 11 is disposed on the surface of the polymer. It can be understood that the copper-clad polymer 2 is prepared by the above-mentioned polymer surface copper-clad method 1, and the polymer can be a base film, a substrate, a matrix, or any combination of the above forms.

[0085] Below, specific embodiments and comparative examples are provided to illustrate the technical features of the present invention.

[0086] In Example 1, the copper-clad polymer 2 is formed by sequentially performing the following steps, including a decontamination step S1 , a roughening step S2 , a sensitization step S3 , a water washing step S4 , an activation step S5 , and a copper plating step S6 .

[0087] Decontamination step S1: First, a polymer base film 10 is placed in a decontamination liquid for the first ultrasonic cleaning, wherein the composition of the decontamination liquid is 30g / L sodium hydroxide, 20g / L sodium carbonate, and 55g / L detergent, the cleaning temperature is 45°C, and the cleaning time is 15-20 minutes; then, 75% alcohol and deionized water are used to perform a second ultrasonic cleaning on the polymer base film 10 for 10 minutes to remove oil or impurities on the original surface of the polymer base film 10; then, the polymer base film 10 is placed in a constant temperature forced air drying oven for drying.

[0088] Roughening step S2: firstly perform a first roughening treatment S21, and then perform a second roughening treatment S22:

[0089] The first roughening treatment S21 is to first perform a plasma treatment S211 and then perform a corona treatment S212; wherein the plasma treatment S211 is to first place the polymer base film 10 into the ion chamber, close the valve of the ion chamber, and evacuate the ion chamber to 5.0×10 -2 Pa; then, nitrogen gas is introduced to make the working gas pressure 1Pa, and the polymer base film 10 is plasma treated with a working power of 150W, a treatment temperature of 25°C, and a treatment time of 1.5 minutes; wherein the corona treatment S212 is performed using a roll-to-roll corona treatment equipment, and the polymer base film 10 is corona treated with a treatment voltage of 35kv and a treatment time of 2.5 minutes.

[0090] The second roughening treatment S22 is to place the polymer base film 10 horizontally into the roughening liquid to perform the second roughening on the polymer base film 10, wherein the roughening liquid is a sodium hydroxide aqueous solution with a mass fraction of 25%, the time of the second roughening treatment is 8 minutes, and the temperature of the second roughening treatment is 25°C; thereafter, the polymer base film 10 is repeatedly washed with deionized water and placed in a blast drying oven for drying.

[0091] Sensitization step S3: placing the polymer base film 10 horizontally into the sensitization solution and soaking it. The sensitizing solution is a 30 g / L stannous chloride solution, the soaking time is 1-2 minutes, and the temperature is 30°C.

[0092] Washing step S4: placing the polymer base film 10 horizontally in deionized water for washing. The temperature of the deionized water is 45° C., and the washing time is 10-15 seconds.

[0093] Activation step S5: placing the polymer base film 10 horizontally into the activation solution and soaking it. The activation solution is a 1.2 g / L palladium chloride solution, the soaking time is 1-2 minutes, the temperature is 25° C., and it is dried.

[0094] Copper plating step S6: placing the polymer base film 10 horizontally into the copper plating solution and immersing it. A copper layer is attached to the surface of the polymer base film 10, the immersion time is 2 minutes, and the immersion temperature is 40°C, wherein the composition of the copper plating solution is 10g / L copper sulfate, 7g / L sodium hydroxide, 25g / L potassium sodium tartrate tetrahydrate, 36g / L citric acid, 40g / L disodium ethylenediaminetetraacetate, 15mL / L formaldehyde, 25mg / L 2'2-bipyridine and 20mg / L potassium ferrocyanide.

[0095] Please refer to Figure 4After the polymer base film 10 undergoes a decontamination step S1, a roughening step S2, a sensitization step S3, a water washing step S4, an activation step S5, and a copper plating step S6, a copper-clad layer 11 is formed on the surface of the polymer base film 10 to become a copper-clad polymer 2.

[0096] Please also refer to Figure 5 and Figure 6 , Regarding the first roughening process S21, Figure 5 This is the SEM image of the polymer base film after corona treatment. Figure 6 This is the SEM image of the polymer base film after plasma treatment.

[0097] In terms of the deposition rate determination, the copper plating step S6 is tested by weighing method: V = (M2-M1) / ρst, M1 is the mass of the polymer base film 10 before copper plating, M2 is the total mass after copper plating, S is the base film area, and ρ is the density of copper 8.96 g / cm 3 , t is the copper plating time.

[0098] In the measurement of copper foil surface density (D), the copper-clad polymer 2 is calculated by weighing; the calculation method is: D = (M2-M1) / s, where M1 is the mass of the base film before copper plating, M2 is the overall mass after copper plating, and s is the area of ​​the base film. The weighing is repeated at least 3 times and the average value is taken.

[0099] In terms of thermal stability, the copper-clad polymer 2 is subjected to a thermal stability test at a test temperature of 150° C. for 30 minutes, including testing whether the copper-clad layer 11 shrinks.

[0100] In terms of copper plating solution stability, after the copper plating step S6, the copper plating solution is evaluated on whether a precipitate is generated, whether the color is changed, and whether it can be used for copper plating again.

[0101] The difference between Example 2 and Example 1 is that in the copper plating step S6, the copper plating solution does not include citric acid.

[0102] The difference between Example 3 and Example 1 is that in the copper plating step S6, the components of the copper plating solution do not include potassium sodium tartrate tetrahydrate.

[0103] The difference between Example 4 and Example 1 is that in the copper plating step S6, the components of the copper plating solution do not include citric acid and potassium sodium tartrate tetrahydrate.

[0104] The difference between Comparative Examples 1 to 4 and Example 1 is that the roughening step S2 In the embodiment, the first roughening treatment S21 is not included; and in the copper plating step S6, Comparative Example 2 does not include citric acid, Comparative Example 3 does not include potassium sodium tartrate tetrahydrate, and Comparative Example 4 does not include citric acid and potassium sodium tartrate tetrahydrate.

[0105] Regarding the differences in technology and efficacy between the above-mentioned Examples 1-4 and Comparative Examples 1-4, The results are summarized in Tables 1, 2 and 3 below.

[0106] Table 1

[0107] At the same time, you can refer to Figures 7 to 10 ,in, Figure 7 The SEM morphology of the copper-clad layer of Example 2, Figure 8 The optical image of the copper clad layer of Example 3, Fig. 9 The SEM morphology of the copper-clad layer of Example 3, Fig.10 This is the optical morphology of the copper foil after copper plating in Comparative Example 2.

[0108] From Table 1, we can first look at Comparative Example 4, which has the worst copper deposition rate. We can further see that compared with Comparative Example 4, Comparative Example 2 and Comparative Example 3 use citric acid or potassium sodium tartrate tetrahydrate in the copper plating solution, which improves the copper deposition rate. However, when we look at Comparative Example 1, which uses citric acid and potassium sodium tartrate tetrahydrate at the same time, although the copper deposition rate is improved, the copper layer density is higher than that of Comparative Example 4.

[0109] Next, it can be seen that in Example 4, the copper deposition rate can be further improved through the first roughening treatment S21, and at the same time, the copper layer density is also significantly reduced; further, it can be seen that in Example 2 and Example 3, the copper layer density is further reduced due to the first roughening treatment S21 and the use of citric acid or potassium sodium tartrate tetrahydrate in the copper plating solution.

[0110] Next, it can be seen that in Example 1, after the first roughening treatment S21, and when citric acid and potassium sodium tartrate tetrahydrate are used simultaneously, the copper layer density is the lowest, that is, the thinnest.

[0111] Table 2

[0112] As shown in Table 2, the degree of bonding between the copper clad layer 11 and the polymer base film 10 or the thermal stability of Examples 1-4 are all good or better, and the obtained copper clad layer 11 is flat and dense.

[0113] In summary, on the one hand, Example 1 can efficiently produce the copper layer with the lowest density. That is, the copper-clad polymer 2 has the lightest and thinnest copper-clad layer 11. At the same time, the copper-clad layer 11 is the smoothest and densest, and has better bonding degree and thermal stability.

[0114] On the other hand, for Examples 1-4, especially Example 1-3, it can be understood that in a single copper plating step S6, a thinner and better copper cladding layer 11 can be obtained in the same time.

[0115] The above are only several preferred embodiments of the present invention, but they cannot be used to limit the patent protection scope of the present invention; therefore, all simple equivalent changes and modifications made according to the patent protection scope of the present invention and the contents of the specification should fall within the patent protection scope of the present invention.

Claims

1. A method for copper coating on a polymer surface, characterized in that: The following steps are involved: A. Roughening step: performing a first roughening treatment on the polymer to obtain a roughened polymer; and B. Copper plating step: copper plating the roughened polymer with a copper plating solution to obtain a copper-clad polymer, wherein the copper plating solution includes a complexing component, the complexing component includes a first plant acid, and the first plant acid includes citric acid, malic acid, glycolic acid, or tartaric acid.

2. The method according to claim 1, characterized in that The complexing component further includes a first phytate, wherein the first phytate includes citrate, malate, glycolate, or tartrate.

3. The method according to claim 2, characterized in that The first plant acid is citric acid, and the first plant acid salt is potassium sodium tartrate.

4. The method according to claim 3, characterized in that The mass ratio of the first phytic acid to the first phytate salt is 1:(0.5-2.0).

5. The method according to claim 2, characterized in that The complexing component further includes a complexing agent, and the complexing agent includes disodium ethylenediaminetetraacetate, 2'2-bipyridine, and potassium ferrocyanide.

6. The method according to claim 5, characterized in that The mass ratio of the first phytic acid to the first phytic acid salt to the complexing agent is 1:(0.5-2.0):(0.5-2.0).

7. The method according to claim 5 or 6, characterized in that The mass ratio of the first plant acid to the disodium ethylenediaminetetraacetic acid is 1:(1.0-1.8).

8. The method according to claim 1, characterized in that The copper plating solution further includes: a copper ion source, a pH value adjuster, and a reducing agent.

9. The method according to claim 1 or 3, characterized in that: The first roughening treatment includes plasma treatment, corona treatment or a combination of any of the above treatments.

10. The method according to claim 9, characterized in that The first roughening treatment includes the plasma treatment and the corona treatment, wherein a ratio of a treatment time of the plasma treatment to a treatment time of the corona treatment is 3:(1-30).

11. The method according to claim 1, characterized in that In the roughening step, a second roughening treatment is further performed after the first roughening treatment to obtain the roughened polymer.

12. The method according to claim 11, characterized in that A sensitization step and an activation step are sequentially performed on the roughening polymer between the roughening step and the copper plating step.

13. The method according to claim 12, characterized in that The polymer is subjected to a decontamination step before the roughening step, and the roughened polymer is subjected to a water washing step between the sensitization step and the activation step.

14. The method according to claim 13, characterized in that In the decontamination step, a decontamination solution is used, which includes sodium hydroxide, sodium carbonate and a detergent. In the second roughening treatment, a sodium hydroxide aqueous solution with a mass fraction of 20-30% is used. In the sensitization step, a stannous chloride aqueous solution with a concentration of 20-40 g / L is used. In the washing step, deionized water with a temperature of 40-50° C. is used. In the activation step, a palladium chloride aqueous solution with a concentration of 0.75-2 g / L is used.

15. The method according to claim 1, wherein: The polymer includes: polyethylene, polytetrafluoroethylene, polyvinylidene fluoride, polyimide, polyethylene terephthalate, polypropylene, polysulfone, polydimethylsiloxane, polyamide, polystyrene, polyvinyl chloride, aramid, polyphenylene diamine, acrylonitrile butadiene styrene copolymer, polybutylene terephthalate, polyparaphenylene terephthalamide, polypropylene, polyamide urea, polyformaldehyde, epoxy resin, phenolic resin, silicone rubber, polycarbonate, polyvinyl alcohol, polyethylene glycol or any combination thereof.

16. A copper-clad polymer, characterized in that: The copper-clad polymer is prepared by the method according to any one of claims 1 to 15.

17. A copper plating solution, characterized in that: Its components include: a first phytic acid and a first phytic acid salt, wherein the first phytic acid is citric acid, the first phytic acid salt is potassium sodium tartrate, and the mass ratio of the first phytic acid to the first phytic acid salt is 1:(0.5-2.0).

18. The copper plating solution according to claim 17, characterized in that Its components further include disodium ethylenediaminetetraacetate, 2'2-bipyridine, and potassium ferrocyanide, wherein the mass ratio of the first plant acid to the disodium ethylenediaminetetraacetate is 1:(1.0-1.8).